Jawabanmu

2014-09-08T21:19:05+07:00
A. -3m+4n - (7n-8m+10)
     = -3m+4n-7n+8m-10
     = 5m-3n-10
b. 15a+7b-5c - (-11a-12b+13d)
    = 15a+7b-5c+11a+12b-13d
    = 26a+19b-5c-13d
1 4 1
2014-09-08T21:21:46+07:00
A) -3m + 4n - 6 - (7n-8m+10) = -3m + 4n - 6 -7n + 8m -10
                                         = -3m + 8m + 4n - 7n - 6 -10
                                         = 5m - 3n - 16
b) 15a+7b-5c - (-11a-12b+13d) = 15a + 7b - 5c + 11a + 12b - 13d
                                           = 15a+11a+7b+12b-5c-13d
                                         = 26a + 19b - 5c - 13d
2 4 2